2012
DOI: 10.5121/ijcsit.2012.4110
|View full text |Cite
|
Sign up to set email alerts
|

Blind 3D Model Watermarking based on Multi-Resolution Representation and Fuzzy Logic

Abstract: Insertion of a text message, audio data or/and an image into another image or 3D model is called as a watermarking process. Watermarking has variety of applications like: Copyright Protection, Owner Identification, Copy Protection and Data Hiding etc., depending upon the type of watermark insertion algorithm. Watermark remains in the content after applying various attacks without any distortions. The blind watermarking method used in the system is based on a wavelet transform, a fuzzy inference system and a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Thus, the fuzzy perceptual mask combines all these non-linear variables to build a simple, easy to use HVS (human visual systems) model. Results showed that the system is robust against affine transformations, smoothing, cropping, and noise attacks [5]. Another blind watermarking scheme based on volume moments was introduced by Wang, et al [6].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the fuzzy perceptual mask combines all these non-linear variables to build a simple, easy to use HVS (human visual systems) model. Results showed that the system is robust against affine transformations, smoothing, cropping, and noise attacks [5]. Another blind watermarking scheme based on volume moments was introduced by Wang, et al [6].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, there have been many watermarking methods proposed for 3D mesh models [4][5][6][7][8][9][10][11][12][13][14]. However, these methods are only useful for the copyright protection of 3D content or visual applications that use 3D content.…”
Section: Introductionmentioning
confidence: 99%
“…3D watermarking schemes are generally focused on geospatial domain and frequency domain [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The main concept of watermarking methods in the geospatial domain is to embed the watermark by modifying the value of vertices or geometric features as length, area or topology features while the main concept of watermarking schemes in the frequency domain is to embed the watermark in the spectrum coefficients of DFT, DWT, and DCT of a sequence of vertices or topologies.…”
Section: D Model Watermarkingmentioning
confidence: 99%